2013
DOI: 10.1159/000346427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Magnesium Supplementation on Carotid Intima-Media Thickness and Flow-Mediated Dilatation among Hemodialysis Patients: A Double-Blind, Randomized, Placebo-Controlled Trial

Abstract: Objectives: The aim of the present study was to determine the efficacy of oral magnesium (Mg) supplementation on endothelial function through evaluation of carotid intima-media thickness (cIMT), brachial artery flow-mediated dilatation (FMD), and C-reactive protein (CRP) among hemodialysis (HD) patients. Methods: This randomized, controlled, double-blind clinical trial consisted of 54 patients on HD. One group was treated orally with 440 mg of Mg oxide 3 times per week for 6 months (n = 29). The control group … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
91
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 36 publications
7
91
0
1
Order By: Relevance
“…In accordance with these findings, a recent study in hemodialysis patients showed that magnesium oxide for 6 months was able to decrease carotid IMT with an increase in the placebo group [57]. Indeed, the role of magnesium in attenuating the progression of atherosclerosis has been previously demonstrated in hemodialysis patients [58].…”
Section: Discussionsupporting
confidence: 61%
“…In accordance with these findings, a recent study in hemodialysis patients showed that magnesium oxide for 6 months was able to decrease carotid IMT with an increase in the placebo group [57]. Indeed, the role of magnesium in attenuating the progression of atherosclerosis has been previously demonstrated in hemodialysis patients [58].…”
Section: Discussionsupporting
confidence: 61%
“…In a trial in hypomagnesemic patients, magnesium improved glycemia after kidney transplantation [48]. In another study, carotid intima-media thickness was decreased after magnesium treatment in patients on hemodialysis [49]. Other studies have shown that magnesium reduces blood pressure [15, 50].…”
Section: Discussionmentioning
confidence: 99%
“…In a small interventional study with 47 HD patients, Mg supplementation was associated with a significant improvement of bilateral carotid intima-media thickness [24]. In a recent randomized double-blinded, placebo-controlled study, Mg supplementation over 6 months also resulted in a decrease of carotid intima thickness, which is possibly due to an inhibition of calcification [25]. Mg seems to influence molecular processes associated with the inhibition of vascular calcification such as a decrease of the calcium entry into the cells of the media, prevention of cell damage (apoptosis) [31] and inhibition of Wnt/β-catenin signaling pathway [32].…”
Section: Discussionmentioning
confidence: 99%
“…In a recent double-blind, randomized, placebo-controlled trial with 54 HD patients, Mg supplementation over 6 months resulted in a decrease of carotid intima-media thickness possibly due to an inhibition of calcification [25]. …”
Section: Introductionmentioning
confidence: 99%